Biomimetic lipid–fluorescein probe for cellular bioimaging - Moon, Hyungkyu; Sultana, Tania; Lee, JeongIk; Huh, Jungrim; Lee, Hae Dong; Choi, Myung-Seok (Frontiers in Chemistry, 2023)
Fluorescence probe is one of the most powerful tools for cellular imaging. Here, three phospholipid-mimicking fluorescent probes (FP1–FP3) comprising fluorescein and two lipophilic groups of saturated and/or unsaturated C18 fatty acids were synthesized, and their optical properties were investigated. Like in biological phospholipids, the fluorescein group acts as a hydrophilic polar headgroup and the lipid groups act as hydrophobic non-polar tail groups. Laser confocal microscope images illustrated that FP3, which contains both saturated and unsaturated lipid tails, showed great uptake into the canine adipose-derived mesenchymal stem cells.